Trinidad. Rope Tree, Botanic Gardens - (:unkn) unknown (My University, 2009)
A picture of a Rope tree with its tangled limbs stretching to the ground.
Colour; Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Rope tree; Botanical gardens